Subcellular Distribution of S-Nitrosylated H-Ras in Differentiated and Undifferentiated PC12 Cells during Hypoxia - Barbakadze, Tamar (Cell J, 2017)
OBJECTIVE: Hypoxia or exposure to excessive reactive oxygen or nitrogen species could induce S-nitrosylation of various target proteins, including GTPases of the Ras-superfamily. Under hypoxic conditions, the Ras-protein is translocated to the cytosol and interacts with the Golgi complex, endoplasmic reticulum, mitochondria. The mobility/translocation of Ras depend on the cells oxidative status. However, the importance of relocated S-nitrosylated-H-Ras (NO-H-Ras) in proliferation/differentiation processes is not completely understood. We have determined the content of soluble- and membrane-bound-NO-H-Ras in differentiated (D) and undifferentiated (ND) rat pheochromocytoma (PC12) cells under hypoxic and normoxic conditions. MATERIALS AND METHODS: In our experimental study, we analyzed NO-H-Ras levels under hypoxic/normoxic conditions in membrane and soluble fractions of ND and D PC12 cells with/without nitric oxide donor, sodium nitroprusside (SNP) treatment. Cells were analyzed by the S-nitrosylated kit, immunoprecipitation, and Western blot. We assessed the action of NO-H-Ras on oxidative metabolism of isolated mitochondria by determining mitochondrial hydrogen peroxide generation via the scopoletin oxidation method and ATP-production as estimated by the luminometric method. RESULTS: Hypoxia did not influence nitrosylation of soluble H-Ras in ND PC12 cells. Under hypoxic conditions, the nitrosylation of soluble-H-Ras greatly decreased in D PC12 cells. SNP didn’t change the levels of nitrosylation of soluble-H-Ras, in either hypoxic or normoxic conditions. On the other hand, hypoxia, per se, did not affect the nitrosylation of membrane-bound-H-Ras in D and ND PC12 cells. SNP-dependent nitrosylation of membrane-bound-H-Ras greatly increased in D PC12 cells. Both unmodified normal and mutated H-Ras enhanced the mitochondrial synthesis of ATP, whereas the stimulatory effects on ATP synthesis were eliminated after S-nitrosylation of H-Ras. CONCLUSION: According to the results, it may be proposed that hypoxia can decrease S-nitrosylation of soluble-H-Ras in D PC12 cells and abolish the inhibitory effect of NO-H-Ras in mitochondrial oxidative metabolism.